THE USE OF DIRECT ANTIGLOBULIN TEST TO DETECT AUTOANTIBODIES IN PATIENTS WITH ANEMIA OF VARIOUS ORIGINS - N. V. Mineeva; I. I. Krobinets; N. N. Bodrova; I. O. Bogdanova (Онкогематология, 2017)
Introduction. Autoantibodies directed against red blood cells (RBCs) are the main cause of hemolysis in patients with autoimmune hemolytic anemia (AIHA) and they can also complicate the course of certain diseases. Various methods are used to detect autoantibodies, but most of all, a polyand monospecific direct antiglobulin test (DAT) is applied. The method is based on the detection of immunoglobulins of G, M, A classes and С3 complement components bound with RBCs surfaces. DAT is used to differentiate between immuno-dependent and immuno-independent anemia. Objective of this study was the analysis of DAT results in patients with various diseases accompanied by anemia.Materials And Methods. Blood samples of patients aged between 5 to 90 years with anemia who underwent examination and/or treatment at the Russian Research Institute of Hematology and Transfusiology of Russian Federal Medical-biological Agency were used as a study material. The results of laboratory testing for the period from 2013 to 2016 were examined and data analysis was performed. The determination of classes of antibodies directed against RBCs was carried out in a direct Coombs reaction using a gel system DiaMed-ID (DiaMed Micro Typing System, Switzerland).Results. The DAT results were positive in patients with AIHA (53 %), paroxysmal nocturnal hemoglobinuria (PNH, 100 %), cryoglobulinemia (62.5 %), chronic lymphoproliferative diseases (CLPD, 27.5 %), multiple myeloma (MM, 23.6 %), anemia of unknown origin (21.4 %), and other autoimmune diseases (19 %). In blood samples of DAT-positive patients, monospecific IgG or C3 complement components, as well as various combinations of Ig with a complement component: IgG + C3, IgG + IgM + C3, IgM + C3, and IgG + IgA, were detected. In our study, positive DAT result was not always associated with laboratory evidence of hemolysis. Among all DAT-positive patients, signs of hemolysis were observed in 53.2 % of cases. Only in patients with AIHA and PNH hemolysis was observed in 100 % of cases.Conclusions. A positive DAT result is one of the criteria for diagnosing of immune hemolytic anemia, however, it does not always indicate an autoimmune pathogenesis of anemia, the presence of specific autoantibodies, and thus is not always associated with hemolysis. Only a comprehensive assessment of a clinical picture and DAT results makes it possible to diagnose the disease.